Sonno, sogni e neuroscienze - Piazzi, Andrea; Clementi, Valentina; Brugnoli, Chiara (Il sogno della farfalla, 2021)
Over the last millennia, dreams have exclusively been considered an object of interpretation. However, during the last decades, neurobiological research on oniric activity has progressively developed in the attempt to investigate the underlying neurophysiological processes. Dreams are strictly connected to the sleep physiological process and neuroscientific studies have greatly contributed to expand the body of knowledge in this field. This article analyzes scientific literature on sleep physiology by further examining the progresses reached on dream neurobiology. The authors finally discuss the main scientific theories on dreams, by criticizing some positions which seem to stem from concepts in contrast with a scientific approach.